Synthesis, Characterization, Antimicrobial and Anticancer Activity of New Bidentate Schiff Base Ligand and their Transition Metal(II) Complexes - Arulmozhi, S.; Sasikumar, G.; Subramani, A.; Sudha, A.; Askar Ali, S.J. (Asian Journal of Chemistry, 2021)
The metal(II) complexes were synthesized by addition of corresponding MCl2 (M = Mn2+, Ni2+, Cu2+ and Zn2+) with 1,2-bis(1H-pyrrol-2-ylmethylene)diazane in methanol. The ligand acts as a bidentate as confirmed from the mass, IR, UV, NMR and EPR spectral studies. The Schiff base ligand forms hexa-coordinated complexes having octahedral geometry for Mn(II), Ni(II), Zn(II) and Cu(II) complexes. The metal complexes showed an excellent antimicrobial activity spectrum in vitro against both Gram-negative (Klebsiella pneumoniae and Acinetobacter baumannii), Gram-positive (Staphylococcus aureus and Enterococcus faecalis) and human pathogenic bacteria isolates. To find the binding affinity with protein BSA kinase, for that molecular docking studies were also carried for all the four synthesized metal(II) complexes. The anticancer activity of the synthesized metal(II) complexes was also screened against the three human tumor cell lines MCF7 human breast adenocarcinoma cell line, CaSki human caucasian cervical epidermoid carcinoma and HCT116 human colon cancer cell lines. The present study showed that Zn(II) complex showed potent inhibition by the ratio of 80% as compared to the inhibition in the normal cells (L-6).